KEPENTINGAN INDONESIA DALAM MENYEPAKATI COMPREHENSIVE ECONOMIC PARTNERSHIP AGREEMENT (CEPA) DENGAN THE EUROPEAN FREE TRADE ASSOCIATION (EFTA) TAHUN 2017-2019 - Anggi Septia Gustrinaldi; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to find out about Indonesia's interests in agreeing on the Comprehensive Economic Partnership Agreement ( CEPA ) with EFTA in 2017-2019. During the years 2017-2019 Indonesia and EFTA have Make a cooperation in various sector in the field of economics . The four EFTA countries are big market opportunities for Indonesia , but these are not yet at optimal conditions. So that through a cooperation agreement within the agreed CEPA framework is able to maximize the benefits to be obtained for both parties. This research uses descriptive qualitative method, with the level of analysis of the nation state, the theory used is the theory of international cooperation in the perspective of liberalism . The author collects data from books, journals, mass media, websites, official documents and MoU which is used to analyze matters of Indonesian interest in agreeing to an agreement with EFTA. Research is showing that during the years 2017-2019 Indonesia and also EFTA make a cooperation in various sector economy . Through this agreement that was agreed to provide a great opportunity for Indonesia to enter the market with low intensity to optimize the benefits to be obtained , as well as the opening of other doors of trade in Indonesian products to Europe through EFTA member countries. This collaboration will certainly have a good impact on both parties.  Keywords  : Indonesian Interests  , CEPA, EFTA , International Cooperation